Anti-Angiogenesis Maintenance Therapy in Newly Diagnosed and Relapsed Ovarian Cancer: A Meta-analysis of Phase III Randomized Controlled Trials - Wang, Yizi; Zhang, Shitai; Song, Zixuan; Ouyang, Ling; Li, Yan (Frontiers in Pharmacology, 2021)
Aim: Anti-angiogenesis agents have been added as maintenance therapy in ovarian cancer over the past decade. The aim of this meta-analysis was to analyze the efficacy of anti-angiogenesis therapy in newly diagnosed and relapsed ovarian cancer. Methods: PubMed, Embase, and Cochrane databases were searched for all phase III randomized controlled trials (RCTs) that assessed the efficacy and toxicity of anti-angiogenesis agents in ovarian cancer. Overall survival (OS) and progression-free survival (PFS) were used to evaluate the effectiveness of anti-angiogenesis therapy in ovarian cancer. Results: A total of 6097 patients with newly diagnosed ovarian cancer from 5 phase III RCTs and 2943 patients with relapsed ovarian cancer from 6 phase III RCTs were included in this meta-analysis. The pooled results showed that anti-angiogenesis significantly improved PFS (hazard ratio [HR], 0.84; 95% confidence interval [CI], 0.76-0.93; P = .001), but not OS (HR, 0.98; 95% CI, 0.91-1.05; P = .49) compared with placebo in newly diagnosed ovarian cancer patients. In relapsed ovarian cancer patients, the pooled results showed a significant improvement on OS (HR, 0.89; 95% CI, 0.82-0.98; P = .02) and PFS (HR, 0.61; 95% CI, 0.52-0.72; P < .001). The pooled results also showed that the anti-angiogenesis agents were associated with an increase in the occurrence of severe hypertension, neutropenia, diarrhea, thrombocytopenia, headache, and bleeding in ovarian cancer. Conclusions: Study results suggest that anti-angiogenesis agents were an effective therapy for relapsed ovarian cancer. Anti-angiogenesis may be associated with some severe but not fatal adverse events.